Automatic sweet pepper detection based on point cloud images using subtractive clustering - Zhao, Xiaokang; Li, Hao; Zhu, Qibing; Huang, Min; Guo, Ya; Qin, Jianwei (International Journal of Agricultural and Biological Engineering, 2020)
Automatic identification and detection of fruit on trees by machine vision is the basis of developing automatic harvesting robots in agriculture. The occlusion of branches, leaves and other fruits in canopy images will affect the accuracy of fruit detection. To provide a scientific and reliable technical guidance for fruit harvesting robots, a method using point cloud images was proposed in this study to detect red fruits to overcome the impact of occlusion on detection. Firstly, the fruit regions were segmented from a tree’s point cloud by applying the color threshold of red and green. Then, the noise in fruit point clouds was removed with sparse outlier removal. Finally, the point cloud of each fruit was detected and counted based on the subtractive clustering algorithm. For the sweet pepper dataset, the true positive rate (TPR) is 90.69% and the false positive rate (FPR) is 6.97% for all fruits that are at least partially visible in the scene. Keywords: sweet pepper detection, point cloud, subtractive clustering, computer vision DOI: 10.25165/j.ijabe.20201303.5460 Citation: Zhao X K, Li H, Zhu Q B, Huang M, Guo Y, Qin J W. Automatic sweet pepper detection based on point cloud images using subtractive clustering. Int J Agric & Biol Eng, 2020; 13(3): 154–160.